Improving Labour Utilisation in Brazil - de Mello, Luiz (OECD Economics Department Working Papers, 2006)
Labour force participation is comparable to the OECD area for prime-age males. It is somewhat lower for females and is trending down for youths as a result of rising school enrolment. The labour market is placing an increasing premium on skills, making it particularly difficult for the less educated to find a job. Labour informality is pervasive and turnover high, especially for the less educated, discouraging investment in labour training and the acquisition of job-related skills, and perpetuating income disparities. The main policy challenge is to improve labour utilisation by reducing informality and fostering human capital accumulation on and off the job. A stable macroeconomy is a pre-condition for reducing unemployment, but a greater focus on activation within the current policy framework would be advisable. To close the remaining gender gap, female labour force participation in full-time jobs could be encouraged by increasing the supply of affordable child care and pre-school education. Labour turnover can be reduced by mitigating the incentives for negotiated separation, which currently arise from the design of severance insurance (FGTS) in the event of unfair dismissal. Skill marketability can be enhanced through the introduction of a national skills certification system, and labour training can become more cost-effective through increased contestability in existing programmes